2016
DOI: 10.1186/s12879-016-1999-8
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus genotype distribution in outbreaks of acute gastroenteritis among children and older people: an 8-year study

Abstract: BackgroundNoroviruses (NoVs) are the most frequent cause of acute gastroenteritis worldwide among people of all ages and the leading cause of gastrointestinal disease outbreaks in various settings. To clarify the differences in epidemic situations among different settings, we investigated epidemiological trends and the distribution of NoV genotypes in Yokohama, Japan.MethodsBetween September 2007 and August 2015, 746 outbreaks of NoV gastroenteritis were reported in kindergarten/nursery schools (K/Ns), primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
2
12
0
2
Order By: Relevance
“…The results suggested that the GII.4 Sydney variant was also associated with gastroenteritis outbreaks at childcare and educational facilities, in cases of food poisoning, and at elderly nursing homes. This finding is compatible with the previous reports [36, 38], which suggested that GII.4 was the most dominant type during the 2006–2014 seasons, whereas a small number of GII.2 were detected in this period [20, 39, 40]. However, GII.2 was the most prevalent type in the 2016/2017 season in various countries, including Germany, France, USA, China, and Japan [16, 17, 25, 26].…”
Section: Discussionsupporting
confidence: 93%
“…The results suggested that the GII.4 Sydney variant was also associated with gastroenteritis outbreaks at childcare and educational facilities, in cases of food poisoning, and at elderly nursing homes. This finding is compatible with the previous reports [36, 38], which suggested that GII.4 was the most dominant type during the 2006–2014 seasons, whereas a small number of GII.2 were detected in this period [20, 39, 40]. However, GII.2 was the most prevalent type in the 2016/2017 season in various countries, including Germany, France, USA, China, and Japan [16, 17, 25, 26].…”
Section: Discussionsupporting
confidence: 93%
“…Schools (primary, secondary, colleges, and other schools) and childcare facilities accounted for 93% of all the norovirus outbreaks reported to PHEESS. A higher percentage of norovirus outbreaks among school and childcare settings was also reported in Japan, Taiwan, and Hong Kong [22,23,24]. This differs, however, from the United States and Europe where acute and long-term healthcare facilities (e.g., nursing homes) were reported as the most common setting for norovirus outbreaks [25,26,27].…”
Section: Discussionmentioning
confidence: 96%
“…Foodborne viral infections exert a significant economic burden globally [ 20 ]. Human norovirus (HuNoV), human adenovirus (AdenoV), human astrovirus (AstroV), and human rotavirus (RotaV) frequently cause acute viral gastroenteritis characterized by abdominal cramps, nausea, vomiting, diarrhea, and fever.…”
Section: Introductionmentioning
confidence: 99%